Brief Report. Issue 6 (November 2015) - Lai, Edward Chia-Cheng; Man, Kenneth K. C.; Chaiyakunapruk, Nathorn; Cheng, Ching-Lan; Chien, Hsu-Chih; Chui, Celine S. L.; Dilokthornsakul, Piyameth; Hardy, N. Chantelle; Hsieh, Cheng-Yang; Hsu, Chung Y.; Kubota, Kiyoshi; Lin, Tzu-Chieh; et al.
<x xml:space="preserve">Abstract</x> Background: This study describes the availability and characteristics of databases in Asian-Pacific countries and assesses the feasibility of a distributed network approach in the region. Methods: A web-based survey was conducted among investigators using healthcare databases in the Asia-Pacific countries. Potential survey participants were identified through the Asian Pharmacoepidemiology Network. Results: Investigators from a total of 11 databases participated in the survey. Database sources included four nationwide claims databases from Japan, South Korea, and Taiwan; two nationwide electronic health records from Hong Kong and Singapore; a regional electronic health record from western China; two electronic health records from Thailand; and cancer and stroke registries from Taiwan. Conclusions: We identified 11 databases with capabilities for distributed network approaches. Many country-specific coding systems and terminologies have been already converted to international coding systems. The harmonization of health expenditure data is a major obstacle for future investigations attempting to evaluate issues related to medical costs.